1998
DOI: 10.1002/1529-0131(199805)41:5<855::aid-art12>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Persistence ofYersinia antigens in peripheral blood cells from patients withYersinia enterocolitica O:3 infection with or without reactive arthritis

Abstract: This study has, for the first time, directly demonstrated that bacterial antigens persist for a long time in patients who develop ReA after Y. enterocolitica O:3 infection. The finding of bacterial HSP in synovial fluid cells could provide a link to the pathogenesis of ReA, since T cell responses of synovial cells have been shown to be directed against that structure. A close similarity between the bacterial and host HSP might contribute to the development of the relatively common, chronic form of this complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 30 publications
5
51
0
6
Order By: Relevance
“…This is similar to the literature reported in Yersinia-triggered ReA (30). Further, the finding of strep cell wall PG-PG after a latent period following infection was not surprising as it is relatively resistant to digestion (14) and such inhibition of effective bacterial clearance may be mediated by antigen-specific interleukin-10 secretion (41).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is similar to the literature reported in Yersinia-triggered ReA (30). Further, the finding of strep cell wall PG-PG after a latent period following infection was not surprising as it is relatively resistant to digestion (14) and such inhibition of effective bacterial clearance may be mediated by antigen-specific interleukin-10 secretion (41).…”
Section: Discussionsupporting
confidence: 88%
“…Although still obscure, the pathogenesis of ARF requires primary infection (organism factor) of the throat by certain serotypes of group A strep (the concept of Rheumatogenicity). M serotypes 1,3,5,6,14,18,19,24,27 and 29 are the most frequently implicated. The pathogenic factor (s) are not known although M protein, the hyaluronic acid capsule, the cell wall-associated groupspecific carbohydrate, and the cell membrane have all been suggested (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the organisms triggering ReA, Chlamydia trachomatis and Yersinia enterocolitica are frequent in western countries. The presence of bacterial Ag (2,3) or DNA (4) in the joint suggests that local Ag may drive the immune response. The recent description of a Th2-cytokine secretion pattern in ReA (5)(6)(7)(8) suggests that an ineffective Th1 response may contribute to bacterial persistence in vivo, because Th1 cytokines such as IFN-␥ and TNF-␣ are crucial for the elimination of both Chlamydia (9,10) and Yersinia (11).…”
Section: R Eactive Arthritis (Rea)mentioning
confidence: 99%
“…Yersinia, and probably also Salmonella, can persist in vivo as indicated by elevated IgA and/or IgM titers (36,37) and by the detection of these pathogens in the peripheral blood for months and even years (40). However, DNA of these bacteria is only rarely detected inside the joint, and it has been suggested that, instead, mucosa and lymph nodes might serve as a reservoir for Yersinia and Salmonella (for discussion, see ref.…”
Section: Bacteria Triggering Reamentioning
confidence: 99%